Anti-PD-1 amplifies costimulation in melanoma-infiltrating Th1-like Foxp3+ regulatory T cells to alleviate local immunosuppression - Fernando Alvarez; Fan Huang; Sonia V Del Rincon; Mikhaël Attias; Tho-Alfakar Al-Aubodah; Roman Istomine; Paige McCallum; Abrahim Sleiman; Tamiko Nishimura; Yasser Riazalhosseini; Ciriaco A Piccirillo (Journal for ImmunoTherapy of Cancer)
Background Immune checkpoint inhibitors targeting programmed cell death protein-1 (PD-1) are the first line of treatment for many solid tumors including melanoma. PD-1 blockade enhances the effector functions of melanoma-infiltrating CD8+ T cells, leading to durable tumor remissions. However, 55% of patients with melanoma do not respond to treatment. As Foxp3+ regulatory T (Treg) cells play an important role in tumor-induced immunosuppression and express PD-1, we hypothesized that anti-PD-1 also increases the functions of melanoma-infiltrating Treg cells, which could be detrimental to treatment efficacy.Methods The cellular and functional dynamics of Treg cells were evaluated in C57Bl/6 Foxp3-reporter mice bearing highly immunogenic and PD-1 blockade-sensitive Yale University Mouse Melanoma Exposed to Radiation 1.7 (YUMMER1.7) tumors. Treg cell responses in tumors and lymphoid compartments were examined throughout tumor growth or therapy and were assessed ex vivo by multiparametric flow cytometry analysis, with in vitro suppression assays using tumor-infiltrating lymphocytes isolated by fluorescence-activated cell sorting (FACS) and in situ through spatial proteomic and transcriptomic profiling.Results In this highly immunogenic melanoma model, anti-PD-1 monotherapy yielded high responders (HRs) and low responders (LRs). We show that the potent CD8+ T cell responses characteristic of HR tumors paradoxically coincide with the expansion of highly-activated, Helios-expressing Treg cells. In both HRs and LRs, Treg cells co-localize with CD8+ T cells in immunogenic regions of the tumor and display potent suppressive capacity in vitro. Further characterization revealed that melanoma-infiltrating Treg cells progressively acquire T-bet and interferon gamma expression, exclusively in HRs, and induction of this T helper cell 1 (Th1)-like phenotype in vitro led to CD8+ T cell evasion from Treg cell-mediated suppression. Using spatial proteomic and transcriptomic profiling, we demonstrate that Treg cells display an increased activity of PI3K/Akt signaling in regions of HR tumors with an elevated CD8:Treg cell ratio.Conclusions PD-1 blockade promotes the expansion of a subset of highly-activated Treg cells coexpressing PD-1 and Helios. While these cells are potently suppressive outside tumor environments, costimulatory and inflammatory signals present in the tumor microenvironment lead to their local acquisition of Th1-like characteristics and loss of suppression of effector T cells.